A questão do politicamente correto em temáticas relativas à homossexualidade e seus reflexos na representação da informação - Cabrera, Miriam Regiane Dutra [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Whereas the ethical aspects involved in the thematic representation to influence the professional librarian and document that the language changes with the inclusion of new perceptions of reality, it is important to analyze the peculiarities of the movement of political correctness as a subsidy to the study of its impacts the representation of information, specifically the themes related to homosexuality. Thus, aiming to contribute to sedimentation in the area of theoretical research in Ethics in the representation of information with regard to issues related to homosexuality, aimed to: a) analyze the peculiarities of the movement of political correctness as a subsidy to the study of their impacts on the representation of information, b) analyze the issues relating to homosexuality as an aid to study their impact on the representation of information, c) identify the international literature of information science that has been dedicated to the confluence between the themes of homosexuality, political correctness and representation information; d) to signal prospects of professional action regarding the representation of information on subjects relating to homosexuality in the context of political correctness. To do so, broke a theoretical approach to the ethical representation of information, from which have been specifically studied the issues of political correctness and the issue of homosexuality under the watchful historical, social and informational. Next, we sought to identify, ma international literature of Information Science (LISA basis) of the last decade, have been treated as issues of representation of information on topics related to the politically correct view of homosexuality, from the political search... (Complete abstract click electronic access below)

Considerando que os aspectos éticos envolvidos na representação temática influenciam o fazer profissional do bibliotecário e que a linguagem documental se modifica com a inserção das novas percepções da realidade, torna-se importante analisar as peculiaridades do movimento do politicamente correto como subsídio ao estudo de seus impactos na representação da informação, mais especificamente nas temáticas relativas à homossexualidade. Desse modo, e visando a contribuir para a sedimentação teórica da área de pesquisa em Ética na representação da informação, no tocante às temáticas relacionadas à homossexualidade, objetivou-se: a) analisar as peculiaridades do movimento do politicamente correto como subsídio ao estudo de seus impactos na representação da informação; b) analisar as temáticas relativas à homossexualidade como subsídio ao estudo de seus impactos na representação da informação; c) identificar a literatura internacional de Ciência da Informação que vem se dedicando à confluência temática entre homossexualidade, politicamente correto e representação da informação; d) sinalizar para perspectivas de ação profissional no que tange à representação da informação em temáticas relativas à homossexualidade em um contexto de politicamente correto. Para tanto, partiu-se de uma abordagem teórica dos aspectos éticos em representação da informação, a partir do que foram especificamente estudadas as questões do politicamente correto e a temática da homossexualidade sob o olhar histórico, social e informacional. Em seguida, buscou-se identificar, ma literatura internacional de Ciência da Informação (base LISA) da última década, como vêm sendo tratadas as questões de representação da informação em temáticas ligadas ao politicamente correto face à homossexualidade, a partir...
Keywords: Ética; Homossexualidade; Ciência da informação; Bibliotecarios